Representation and beyond; Female victims in Post-Suharto media - Sushartami, Wiwik (Wacana, Journal of the Humanities of Indonesia, 2012)
This study analyses representations of female victims in post-Suharto media. In so doing, it underlines the import of the fall of the New Order regime and the concurrent opening up of the media world in Indonesia. The study is based on notably influential issues that emerged among media producers, feminist activists, social scientists, policy makers, and general audiences during the period of study (1998-2004). Based on observations made in women's NGOs and other institutions concerned with women, interviews and informal conversations with individuals engaged in projects related to female mediation, and content analysis of a large number of mainstream and alternative media presentations, this study finds that the context of the reform (reformasi) in Indonesia constituted a major factor in influencing the changes that affected women and the media, and more importantly, on the burgeoning of the discourse of female victimization. This study also addresses the concepts of ideology, interpellation, identity, and agency to show how the media culture during the reform period, or rather the cultural producers during that time, constructed female victims' identities by sorting out and selecting the representations that represented the context and the history of the regime's change